Efficiency and productivity analysis for intermediary institutions: Turkish capital markets case - Güler Aras; Yasemin Karaman; Evrim Hacioglu Kazak (Journal of Capital Markets Studies (JCMS), 2020)
Purpose-The purpose of this study is to investigate efficiency and productivity of Turkey's both brokeragesector and intermediary institutions (IIs) that have been active in Turkish capital markets.Design/methodology/approach-Data envelopment analysis (DEA) and Malmquist total factorproductivity index (MPI) are used to analyze efficiency and productivity of Turkey's both brokerage sectorand 51 Turkish IIs constantly operated between the years 2008 and 2018. Paid-in capital, administrativeexpenses and trading volumes are used as input, while net trading commissions and net profit/loss are used asoutput in analysis. The calculations of this analysis are made with DEAP 2.2 program and Python.Findings-The results reveal that during the analysis period, percentage of efficient institutions among 51 IIswas between 18% and 39% while the sector's mean efficiency score ranged between 52% and 65%. While 2009is the year with the highest number of efficient institutions, 2013 is observed to be the least. Finally, the resultsof productivity analysis indicate that all types of IIs are not fully productive during the related period. Thestriking finding obtained is that though there is a decrease in total productivity change, the technologicalchange has a positive effect on their productivity change.Originality/value-This study is a double-layered research paper that includes efficiency analysis by DEA inthe first step and productivity analysis by using MPI in the second step.
Keywords: 330; Efficiency; Capital markets; Productivity; Data envelopment analysis; Intermediary institutions; Malmquist total factor productivity index